PENGUJIAN DIMENSI KONSTRUK LITERASI KEUANGAN MAHASISWA - Setiawati, Setiawati; Nurkhin, Ahmad (Universitas Negeri Semarang, 2017)
The purpose of this study is to examine the dimensions of students’financial literacy construct consisting of financial knowledge, financial attitude, financial behavior. This research is quantitative research with students are population of Faculty of Economics 965 and sample of 283 students is taken with propotionate random sampling technique. The method of taking data are question and questionnaire. Analysis used is descriptive analysis and structural equational modeling (SEM).The result showed that (1) the construction of financial literacy can be explained by the dimension of financial knowledge, dimension of financial attitude, and dimension of financial behavior, (2) there was no influence of financial knowledge to student’s financial behavior, (3) there was a significance influence of financial attitude toward students’s fianacial behavior, (4) there was a correlation between financial knowledge and financial attitude of student of Faculty of Economy